First person - Mayra Fernanda Martínez-López (The Company of Biologists, 2024)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping researchers promote themselves alongside their papers. Mayra Fernanda Martínez-López is first author on ' Macrophages directly kill bladder cancer cells through TNF signaling as an early response to BCG therapy', published in DMM. Mayra conducted the research described in this article while a PhD student in Dr Rita Fior's lab at Champalimaud Foundation, Lisbon, Portugal. She is now an associate professor and principal investigator at the Faculty of Medicine, Universidad de las Américas Ecuador, Quito, Ecuador, investigating the effects of the innate immune system in cancer development and treatment, and its potential therapeutical implications for personalized medicine.